Beyond the bicycle: Seeing the context of the gender gap in cycling. (September 2020) - Shaw, Caroline; Russell, Marie; Keall, Michael; MacBride-Stewart, Sara; Wild, Kirsty; Reeves, Dory; Bentley, Rebecca; Woodward, Alistair
Abstract: Background: In most countries women cycle less than men. This is despite the clear environmental and health benefits of active commuting. Feminist critiques suggest this gender gap reflects societal roles and values, yet there has been little empirical research on the differences in men's and women's cycling in the context of total travel. Methods: Regression analyses were used to explore the travel mode and distance travelled of 49 965 participants in the nationally representative, continuous, cross-sectional New Zealand Household Travel Survey (2002–2014). Regular cyclists were people who cycled at least 10 days in the preceding month. We reported results by gender and cyclist status. Results: Car was the dominant mode of travel for all groups. While fewer women regularly cycled (2%) compared to men (5%), women travelled less each day (12–17% less distance) and were more likely to use public transport and walk than men. These gender patterns were broadly replicated in people who were regular cyclists. Women made 17–47% more motorised trips of less than 5 km than men each day. Overall half of regular cyclists achieved 600 METS or above per week through travel related physical activity, compared to 11–15% of non-regular cyclists. Even after full model adjustment men had more than twice the odds (OR 2.58 (95%CI:2.29–2.92)) of cycling compared to women. Conclusions: Men are more likely to cycle than women in NZ and cyclists get more physical activity. Nonetheless, analysis across all travel (irrespective of regularity of cycling status) suggests that women use more diverse travel modes and generate lower greenhouse gas emissions than men. Better consideration of the social processes shaping travel is needed to create policy, institutions, programmes and infrastructure that achieve the long term goals of the transport system, such as increasing cycling and reducing greenhouse gas emissions. Highlights: Gender differences in cycling are common in low prevalence cycling jurisdictions. Gender differences in overall travel are also common. Overall women travel less and use more diverse modes than men each day. Women who cycle also travel less and use more diverse modes than men. Transport policy needs to take gender into account to promote system change.